2015
DOI: 10.1167/iovs.14-14233
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Adenosine Monophosphate Activates Retinal Apolipoprotein A1 Expression and Inhibits Myopic Eye Growth

Abstract: The 8-Br-cAMP robustly inhibited development of lens-induced myopia. The increase in retinal ApoA1 observed in cAMP-treated and hyperopic eyes suggested a possible interplay between ApoA1 and cAMP in regulating eye growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…MiR-15b and miR-16 have been shown to play a role in suppressing insulin resistance by reducing TNF α and SOCS3 signaling and increasing IGFBP-3 expression. This protects the retinal endothelial cells (REC) against hyperglycemia-induced apoptosis and has been identified as a potential therapeutic target for the treatment of diabetic retinopathy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-15b and miR-16 have been shown to play a role in suppressing insulin resistance by reducing TNF α and SOCS3 signaling and increasing IGFBP-3 expression. This protects the retinal endothelial cells (REC) against hyperglycemia-induced apoptosis and has been identified as a potential therapeutic target for the treatment of diabetic retinopathy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,17 A recent study demonstrated that stimulation of cAMPdependent protein kinase induced by 8-Br-cAMP intravitreal injections reduced myopia progression in a negative lensinduced model to such an extent that it resulted in a hyperopic refraction in chicks. 34 This study also showed that positive lens defocus inhibited ocular growth and increased both retinal cAMP and ApoA1 levels. These results differ from those previously reported by our group, in which the putative rise in scleral cAMP levels induced by FSK had no additional effect on the refraction induced by FD, and the retinal cAMP levels were unaltered in these guinea pigs.…”
Section: Discussionmentioning
confidence: 60%
“…Aspartate receptors were implicated in myopia development by at least two studies [ 60 , 61 ]. Nitric oxide and cAMP signaling were also suggested to play a role in the development of myopia by several studies in chickens [ 37 39 ]. Dopamine signaling has long been associated with experimental myopia and refractive eye development [ 40 ].…”
Section: Discussionmentioning
confidence: 99%